2019
DOI: 10.3389/fpls.2019.00179
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoid Esters Are the Major Constituents From Leaf Lipid Droplets of Camellia sinensis

Abstract: Lipid droplets (LDs) have been widely found from diverse species and exhibit diverse functions. It remains unexplored what potential roles they played in tea. To address this question, we analyzed the chemical composition and the dynamic changes of cytosolic LDs during leaf growth and diurnal cycle. Using TopFluor cholesterol and Nile Red staining we demonstrated that cytosolic LDs were heterogeneous in tea tree ( Camellia sinensis cv. Tieguanyin ); the size and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Zhu et al (2018) found that the cuticle from the mature tea leaves is dominated by triterpenoids and sterols which are absent from that of the tender tea leaves. Zhou et al (2019) also reported that triterpenoid ester content increased with leaf maturation. It is worth noting that the triterpenoid distribution pattern is in sharp contrast with caffeine, which is higher from the tender leaves than that of mature leaves (Ashihara et al, 2008).…”
Section: The Roles Of Tea Leaf Cuticle In Biotic Stressesmentioning
confidence: 88%
“…Zhu et al (2018) found that the cuticle from the mature tea leaves is dominated by triterpenoids and sterols which are absent from that of the tender tea leaves. Zhou et al (2019) also reported that triterpenoid ester content increased with leaf maturation. It is worth noting that the triterpenoid distribution pattern is in sharp contrast with caffeine, which is higher from the tender leaves than that of mature leaves (Ashihara et al, 2008).…”
Section: The Roles Of Tea Leaf Cuticle In Biotic Stressesmentioning
confidence: 88%
“…Lipid droplets were stained with TopFluor ® cholesterol essentially as described in Zhou et al. (2019) .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, AAs, flavonoids, phenolic acids, purine alkaloids, catechins, and caffeine are highly related to green tea [ 17 , 18 , 19 ], it is unclear whether other types of compounds exist in XYMJ green tea. Chen et al demonstrated that steroids and triterpenes are the main compounds present in tea leaves [ 20 ]. Until now, the contents of AAs contributing to quality characteristics in XYMJ related to tea growth and material foundation are still uncertain.…”
Section: Introductionmentioning
confidence: 99%